Dynamic log file analysis: An unsupervised cluster evolution approach for anomaly detection. Issue 79 (November 2018) - Landauer, Max; Wurzenberger, Markus; Skopik, Florian; Settanni, Giuseppe; Filzmoser, Peter
Abstract: Technological advances and increased interconnectivity have led to a higher risk of previously unknown threats. Cyber Security therefore employs Intrusion Detection Systems that continuously monitor log lines in order to protect systems from such attacks. Existing approaches use string metrics to group similar lines into clusters and detect dissimilar lines as outliers. However, such methods only produce static views on the data and do not sufficiently incorporate the dynamic nature of logs. Changes of the technological infrastructure therefore frequently require cluster reformations. Moreover, such approaches are not suited for detecting anomalies related to frequencies, periodic alterations and interdependencies of log lines. We therefore propose a dynamic log file anomaly detection methodology that incrementally groups log lines within time windows. Thereby, a novel clustering mechanism establishes links between otherwise isolated collections of clusters. Cluster evolution techniques analyze clusters from neighboring time windows and determine transitions such as splits or merges. A self-learning algorithm then detects anomalies in the temporal behavior of these evolving clusters by analyzing metrics derived from their developments. We apply a prototype in an illustrative scenario consisting of a log file containing known anomalies. We thereby investigate the influences of certain parameters on the detection ability and the runtime. The evaluation of this scenario shows that 61.8% of the dynamic changes of log line clusters are correctly identified, while the false alarm rate is only 0.7%. The ability of efficiently detecting these anomalies while self-adjusting to changes of the system environment suggests the applicability of the introduced approach.